Pengembangan Bahan Ajar IPAS Berbasis SETS terhadap Keterampilan Berpikir Kreatif siswa Pada Pembelajaran Berdiferensiasi Sekolah Dasar - Nurazizah, Aulia; Uswatun, Din Azwar; Nurasiah, Iis (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop IPAS teaching materials based on Science, Environment, Technology, and Society (SETS) integrated with differentiated learning to enhance elementary school students' creative thinking skills. The research employs the Research and Development (R&D) method with a 4D design (Define, Design, Develop, Disseminate). The research subjects consist of 17 fifth-grade students from SD Aisyiyah Sukabumi. The instruments used include interviews, questionnaires, and tests. Data were analyzed using validity, feasibility, and effectiveness tests. Validation was conducted by four experts (media, material, and practitioners). The results indicate that the teaching materials are highly valid, with an average score of 96% from experts and 94% from practitioners. The effectiveness test, conducted through N-Gain analysis, shows an increase in creative thinking skills with an average score of 0.60 (moderate category). The scores for creative thinking indicators include fluency (20.59), originality (16.29), elaboration (23.35), and flexibility (17.35). The SETS approach allows students to connect learning with real-world issues, while differentiated learning ensures alignment with individual needs. This study demonstrates that IPAS teaching materials based on SETS are effective, relevant, and innovative in improving the quality of elementary education. Its contributions include a teaching material model applicable for educators, a systematic learning guide, and an enhancement of students' creative thinking skills through a contextual approach.